The rational design of international institutions - Koremenos, Barbara; Lipson, Charles; Snidal, Duncan (Cambridge, UK ; New York : Cambridge University Press, 2004)
International institutions vary widely in terms of key institutional features such as membership, scope, and flexibility. This books argues that this is so because international actors are goal-seeking agents who make specific institutional design choices to solve the particular cooperation problems they face in different issue-areas.
The Institutional Features of the Prisoners of War TreatiesInstitutions for Flying: How States Built a Market in International Aviation Services; Driving with the Rearview Mirror: On the Rational Science of Institutional Design; Rational Design: Looking Back to Move Forward; References.
Previously published as a special issue of International organization, v. 55, no. 4, 2001.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: International organization; Organisation internationale; LAW -- International; International organization; Internationale organisaties; Institutionalisme